Scary close : dropping the act and finding true intimacy - Miller, Donald, 1971- (Nelson Books, 2014)
"After decades of failed relationships and painful drama, Donald Miller decided had had enough. Impressing people wasn't helping him connect with anyone. He'd built a life of public isolation, yet he dreamed of meaningful relationships. So at forty years old he made a scary decision: to be himself no matter what it cost."--Amazon.com.